Removal of iron and organic substances from groundwater in an alkaline medium - Krupińska, Izabela (Journal of Environmental Engineering and Landscape Management, 2019)
The article discusses the effectiveness of alkalinisation with calcium hydroxide or sodium hydroxide in the treatment of groundwater from Quaternary formations with an increased content of total iron (up to 6.82 mgFe/dm3) and organic substances (TOC up to 5.60 mgC/dm3). The aim of the research was to determine the effectiveness of the groundwater treatment, in particular, the removal of iron and organic substances in the sorption process and co-precipitation with calcium carbonate and magnesium hydroxide. The correction of the reaction was carried out with aqueous solutions of calcium hydroxide and sodium hydroxide in the pH range from 8.5 to 10.5. As the pH of the water increased, the efficiency of its treatment increased. The treatment results depended on the type of alkalizing reagent, especially in the case of removal of organic substances, reduction of colour and organic substances fixed in iron-organic complexes. Higher suitability of calcium hydroxide than sodium hydroxide in alkalinisation has been demonstrated. Calcium ions introduced into the treated water together with calcium hydroxide probably neutralized organic anions fixed in iron-organic complexes and determining colour and TOC, increasing their susceptibility to adsorption.